Contribuições de Samuel Lowrie e Dina Lévi-Strauss ao Departamento de Cultura de São Paulo (1935 1938) - Cerqueira, Vera Lúcia Cardim de (2010)
This study intends to analyze the contributions of Samuel Harman Lowrie and Dina Lévi-Strauss to the Department of Culture of São Paulo during the period of administration of Mário de Andrade, between the years 1935 and 1938. Both were directly or indirectly representative of the theoretical thoughts and trends which provided a synthesis of the influences for Brazilian Social Sciences along the years: the North-American and the European lineages. The North-American sociologist Samuel Harman Lowrie was hired by the Escola Livre de Sociologia e Política and by the São Paulo City Administration, and developed a study in the area of Sociology and its practical applications, whereas the French ethnologist Dina Lévi-Strauss, with the support and trust from Mário de Andrade, conduced actions in the area of Ethnography, aiming at the possibility of obtaining reconnaissance in her professional life. During a short period, these two scholars allowed the simultaneity of theoretical reflections and practical actions in the universe of public policies, since they believed that Brazil was a favorable place for the development of scientific research